2019
DOI: 10.2147/dmso.s197159
|View full text |Cite
|
Sign up to set email alerts
|

<p>Barriers of medication adherence in patients with type-2 diabetes: a pilot qualitative study</p>

Abstract: Background: Patients with type-2 diabetes have poor adherence to the therapeutic regime. It can result in various complications in body systems associated with undesirable metabolic control. Purpose: The present study aimed to explore the inhibitors of medication adherence in patients with type-2 diabetes. Patients and methods: This was a qualitative study using a conventional content analysis method. Participants were 12 patients with type-2 diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 25 publications
7
47
2
3
Order By: Relevance
“…Hence, implications for the Thai context should train health workers and multidisciplinary teams with an explicit focus on eliciting patient's feelings, beliefs and concerns about illness, and involve patients and their families in decision-making [32]. Rezaei et al suggest that gaining the patient's trust can promote the relationship and medical teams should attempt to tailor care programs to each patient based on their lived experiences and unique challenges to increase their adherence to treatment [33]. An easy plan of treatment, specific to each patient's lifestyle, and acknowledging an individual's limitation due to social isolation, age or limited health literacy [28] can help ensure that taking medication is a part of routine, daily activities.…”
Section: Attitudes Toward Health Care Teammentioning
confidence: 99%
“…Hence, implications for the Thai context should train health workers and multidisciplinary teams with an explicit focus on eliciting patient's feelings, beliefs and concerns about illness, and involve patients and their families in decision-making [32]. Rezaei et al suggest that gaining the patient's trust can promote the relationship and medical teams should attempt to tailor care programs to each patient based on their lived experiences and unique challenges to increase their adherence to treatment [33]. An easy plan of treatment, specific to each patient's lifestyle, and acknowledging an individual's limitation due to social isolation, age or limited health literacy [28] can help ensure that taking medication is a part of routine, daily activities.…”
Section: Attitudes Toward Health Care Teammentioning
confidence: 99%
“…Included studies were published between 2009 and 2019. Five articles [17][18][19][20][21] focused on patients, two [22,23] on healthcare providers/experts, and five on mixture of these groups. The total population sample included 188 patients, 2 relatives, and 25 healthcare providers/experts.…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%
“…Several patients reported misunderstanding with family members about their situation [24]. Some of them reported that they are being ignored by family members [20]. Moreover, family members were also seen as a barrier to the diabetes related healthy lifestyles.…”
Section: Insufficient Family Supportmentioning
confidence: 99%
See 2 more Smart Citations